PP65 antigenemia in the diagnosis of cytomegalovirus infection in AIDS patients - Capela, R. C. [UNESP] (2012)
Cytomegalovirus causes significant morbidity and mortality in AIDS patients and those having undergone bone marrow or another transplant. PP65 antigenemia is based on detecting viral antigen in peripheral blood leukocytes through immunochemistry and by monitoring the infection in immunocompromised individuals. The present study aimed to set up this diagnostic technique in AIDS patients with active cytomegalovirus infection and verify its occurrence in the Botucatu region of São Paulo state, Brazil. Fifty patients, 35 men and 15 women aged from 24 to 69 years, were recruited from those attended at the Department of Tropical Diseases of Botucatu Medical School, UNESP, and divided into three groups according to CD4+ T lymphocyte counts and antiretroviral treatment. The control group comprised bone marrow transplant patients. Fourteen AIDS patients with low CD4+ cell counts tested positive for PP65 antigenemia, which could predict cytomegalovirus infection and indicate prophylactic treatment.